Mechanism of health literacy impact on self-management behaviors in patients with chronic disease: a self-efficacy mediated model moderated by disease duration - Chen, Shichen; Wang, Yike; Liu, Wenjing; Zhang, Die; Zhu, Jinghui; Liu, Guilin (Frontiers in Public Health, 2025)
IntroductionSelf-management behaviors are vital in chronic disease prevention and management, with self-efficacy acting as a key mediator between health literacy and these behaviors. However, disease duration may amplify or attenuate health literacy's impact on self-efficacy—either through experiential learning or management fatigue—requiring empirical validation of its moderating role. This study thus applied a moderated mediation framework to investigate how multidimensional health literacy influences self-management via self-efficacy, and whether disease duration moderates the health literacy–self-efficacy pathway, aiming to clarify efficacy belief dynamics in long-term adaptation.MethodsA cross-sectional study of 601 patients with chronic disease in Wenzhou's Ouhai District assessed health literacy, self-efficacy, and self-management. Using Hayes' PROCESS macro (Model 4 for mediation analysis and Model 7 for moderated mediation analysis, with 5,000 bootstrap iterations).ResultsWe found that self-efficacy partially mediated the relationship between health literacy and self-management behaviors (ES = 0.082, 95%CI: 0.055–0.110; 22.601% of total effect). Crucially, disease duration positively moderated the effect of health literacy on self-efficacy (B = 0.014, p < 0.05, 95%CI: 0.002–0.026), strengthening the indirect effect of health literacy on self-management through self-efficacy as duration increased.DiscussionThese findings demonstrate that self-efficacy mediates the health literacy–self-management link, while disease duration enhances health literacy's effect on self-efficacy, supporting stage-specific precision interventions.